Pelatihan Pembukuan Sederhana dengan Pendekatan Komunikasi Interpersonal Bagi Kelompok Tani Hutan Rumah Madu Sejahtera Kabupaten Pasaman - Sari Fitri; Rizka Ar Rahmah; Marlina Marlina (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
Simple bookkeeping is a means to organize income and expenditure in lower-middle businesses. Kelulud beekeepers are a part of small and medium-sized enterprises. Simple bookkeeping is very easy to apply at the level of Kelulud bee farmers since it involves the use of straightforward recording using four columns that specify income and expenditure, thus showing significant results and streamlining the farmers’ effort in managing their finances. The training was carried out by explaining in details each column and its function when recording financial transactions. Seven out of ten Kelulud beekeepers participating in this seven-day training managed to fully understand the application of simple bookkeeping methods, while three others showed the need for further training. The application of simple bookkeeping is such a .l;kiouseful practice for farmers in managing their expenditure and income that the business they run can develop well.